2004
DOI: 10.2337/diabetes.53.3.597
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Voltage-Gated Potassium Channels in Human and Rhesus Pancreatic Islets

Abstract: Voltage-gated potassium channels (Kv channels) are involved in repolarization of excitable cells. In pancreatic ␤-cells, prolongation of the action potential by block of delayed rectifier potassium channels would be expected to increase intracellular free calcium and to promote insulin release in a glucose-dependent manner. However, the specific Kv channel subtypes responsible for repolarization in ␤-cells, most importantly in humans, are not completely resolved. In this study, we have investigated the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(102 citation statements)
references
References 51 publications
7
94
0
Order By: Relevance
“…The second type of K + current is of the delayed-rectifier type and sensitive to TEA and the Kv2.1/2.2 specific antagonist stromatoxin. This confirms a previous study reporting expression of Kv2.2 in human delta cells [17]. Inhibition of the sustained outward K + current using TEA increased action potential duration and amplitude and stimulated/tended to stimulate somatostatin secretion at 1 and 6 mmol/l glucose ( Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The second type of K + current is of the delayed-rectifier type and sensitive to TEA and the Kv2.1/2.2 specific antagonist stromatoxin. This confirms a previous study reporting expression of Kv2.2 in human delta cells [17]. Inhibition of the sustained outward K + current using TEA increased action potential duration and amplitude and stimulated/tended to stimulate somatostatin secretion at 1 and 6 mmol/l glucose ( Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Expression of Kv2.2 and Kv2.1 channels in human islets has been reported previously [13,17]. Stromatoxin reduced the peak and sustained outward currents during 500 ms depolarisations to 0 mV by 62±10% and 96±2%, respectively (p<0.05, n=4), without affecting the A current ( Fig.…”
Section: Immunohistochemical Localisation Of Delta Cells In Human Pansupporting
confidence: 77%
“…The presence of several Kv channel isoforms has been reported in an alpha cell line [6,8], and in human [9] and mouse [10] alpha cells, including mRNA transcript or protein production of Kv2.1, Kv3.1, Kv3.2, Kv3.3, Kv4.3, Kv6.1 and Kv6.3. In human islets, Braun et al [15] reported the presence of mRNA transcript for Kv2.1 and Kv2.2, and although this data is not specific to alpha cells, they also reported high expression of BK channels.…”
Section: Discussionmentioning
confidence: 99%
“…Like insulin-secreting beta cells, alpha cells possess robust voltage-dependent K + (Kv) currents, which are believed to participate in action potential repolarisation [3][4][5][6][7]. Levels of several Kv channel isoforms, including mRNA transcript or protein levels of Kv2.1, Kv3.1, Kv3.2, Kv3.3, Kv4.3, Kv6.1 and Kv6.3, have been reported in alpha cell lines [6,8] and primary human [9] and mouse [10] alpha cells, although the functional contribution of these to alpha cell Kv currents is not well established.…”
Section: Introductionmentioning
confidence: 99%
“…Eleven subfamilies of this channel are known to exist in mammals. In a detailed study by Yan and coworkers K v2.1 , K v3.2 , K v6.2 , and K v9.3 were found on β cells whereas K v3.1 and K v6.1 were found on α cells and K v2.2 on δ cells of human islets (Yan et al, 2004). A summary of expression the various K v families in insulinoma cells and rat islets has been compiled by .…”
Section: Potassium Channelsmentioning
confidence: 99%